2019
DOI: 10.1002/fsn3.1274
|View full text |Cite
|
Sign up to set email alerts
|

Review on contribution of indigenous food preparation and preservation techniques to attainment of food security in Ethiopian

Abstract: One of the main challenges facing Ethiopia today is ensuring food security, as the country demands more food than before with the increase in population. Although the country's production is much lower than the national demand, there are high postharvest food losses, largely due to limited food processing, preservation, and storage capacity. Universities and research centers in the country had been done and doing research on the postharvest activities to assure effective and sustainable methods of food securit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 54 publications
(113 reference statements)
0
45
0
Order By: Relevance
“…This finding together with the above also indicates that farmers are wealth in different homegrown knowledge in association with pest protection, the associated loss and food insecurity. Similarly, it was also revealed that one way of reducing huge loss by pest infestation and improvement of income and food security is recognition, promotion, and utilization of indigenous knowledge, skills, and practices of farmers that they developed in handling, processing, preservation, and storage of food grains (Kuyu and Bereka, 2020). Proper drying of food grains prior to storage was also reported to be one of the cultural control methods in which farmers in Ethiopia has been using to control pest infestation by reducing moisture content (Getu, 1993;Kuyu and Bereka, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding together with the above also indicates that farmers are wealth in different homegrown knowledge in association with pest protection, the associated loss and food insecurity. Similarly, it was also revealed that one way of reducing huge loss by pest infestation and improvement of income and food security is recognition, promotion, and utilization of indigenous knowledge, skills, and practices of farmers that they developed in handling, processing, preservation, and storage of food grains (Kuyu and Bereka, 2020). Proper drying of food grains prior to storage was also reported to be one of the cultural control methods in which farmers in Ethiopia has been using to control pest infestation by reducing moisture content (Getu, 1993;Kuyu and Bereka, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, losses of food grains such as faba bean due to insect pests during storage has been reported to be one of the major causes of food insecurity of people living in the developing world, including Ethiopia (Hiruy, 2018). One way of reducing such huge loss and improvement of income and food security has been indicated to be recognition, promotion, and utilization of indigenous knowledge, skills, and practices of farmers that they developed in handling, processing, preservation, and storage of food grains (Okoye and Oni, 2017;Kuyu and Bereka, 2020). Therefore, prior to designing and implementation of any insect pest control intervention strategies, it is very vital to assess the status insect pest, degree of losses that have happened, indigenous methods and pest management practices used by the farmers during storage of their grains (Togola et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the lack of sustainability of ARF skill support, perceived time constraints, unsuitable demonstration and cooking methods, and variability of the effective demonstration group size were potential barriers to the expanded use of ARF. Germination is an indigenous food processing method [ 44 ] used in Ethiopia [ 45 ] but with a low rate of use for complementary foods. This holds for our study and Southern Ethiopia [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethiopian farmers, especially smallholding farmers, use traditional storage facilities, which are constructed using local materials. A significant number of farmers use underground-pit storage constructed inside the house or outside with wooden protective shade [ 43 ]. The pit dug is made to be narrow on the top, with the inside part covered with a slurry of cattle dung to prevent any leaks.…”
Section: Agro-ecology Climate and Storage Conditions In Ethiopiamentioning
confidence: 99%